2015
DOI: 10.1039/c5ay01501d
|View full text |Cite
|
Sign up to set email alerts
|

In situ simultaneous investigation of the transport of phenanthrene and fluoranthene adsorbed onto the root surfaces to tissues of mangrove seedlings

Abstract: A novel method for the simultaneous in situ determination of phenanthrene (Phen) and fluoranthene (Fla) adsorbed onto mangrove root surfaces was established using laser-induced time-resolved nanosecondfluorescence spectroscopy combined with a first-order derivative fluorometry (D-LITRF) method. The linear dynamic range, detection limit and recoveries of D-LITRF and laser induced time-resolved nanosecond fluorescence spectroscopy (LITRF) were of the same order. Using the established method, the transport of Phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…0.0087 g/cm 2 , 9.53 cm for Trigonella foenum-graceum and 29.50 cm, 0.0087 g/cm 2 for Brassica juncea). Shoot length decreased with doses of 50 mg/kg (58.43 cm), 200 mg/kg (54.63 cm) and 400 mg/kg (52.63 cm) in Brassica juncea, whereas in Trigonella foenum-graceum, [19,20,23,28]. Many research studies have reported that the accumulation of PAHs in plants is negligible [16,32].…”
Section: Growth Parametersmentioning
confidence: 99%
“…0.0087 g/cm 2 , 9.53 cm for Trigonella foenum-graceum and 29.50 cm, 0.0087 g/cm 2 for Brassica juncea). Shoot length decreased with doses of 50 mg/kg (58.43 cm), 200 mg/kg (54.63 cm) and 400 mg/kg (52.63 cm) in Brassica juncea, whereas in Trigonella foenum-graceum, [19,20,23,28]. Many research studies have reported that the accumulation of PAHs in plants is negligible [16,32].…”
Section: Growth Parametersmentioning
confidence: 99%